Manufacturing and characterization of bipolar fuel cell plate with textile reinforced polymer composites. (January 2015) - Jiang, Bingyan; Stübler, Nacera; Wu, Wangqing; Li, Qingxin; Ziegmann, Gerhard; Meiners, Dieter
Highlights: Textile reinforced polymer composites are qualified by an enhanced VARTM process. Bipolar fuel cell plate is manufactured based on textile reinforced polymer composites. The bipolar fuel cell plate has an improved flexural strength in the range of 166.6–188.3 MPa. The bulk electric conductivity is significantly influenced by the textile design and nanofillers. The maximum achieved bulk electric conductivity is 5902 Sm −1 in the present study. Abstract: An enhanced Vacuum Assisted Resin Transfer Molding (VARTM) process was studied for the manufacturing and characterization of bipolar plate with textile reinforced polymer composites. Rapid qualitative evaluation and quantitative characterization were conducted respectively to achieve an optimal manufacturing process design. The influence of process variables including pre-compaction cycle, post-filling time, curing pressure, etc., on the geometrical and mechanical properties of the textile reinforced polymer composites were investigated. The empirical optimized process design was then adapted for manufacturing of bipolar plate. The electrical properties of the bipolar plate were characterized by measuring its bulk (in-plane) conductivity according to the conventional four probe method. The influence of process conditions, carbon fabric design and nanofillers on the electrical properties of the bipolar plate were considered. The results show that the bipolar plate has a flexural strength in the range of 166.6–188.3 MPa, which is a great improvement in comparison with the one based on highly filled or cut fibres reinforced polymer composites. However, the maximum bulk conductivity achieved is limited at 5902 Sm −1 in this study, suggesting that further development effort is required for bipolar plate manufactured by textile reinforced polymer composites.